Sublethal effects of some botanical and chemical insecticides on the cotton whitefly, Bemisia tabaci (Hem: Aleyrodidae) - Fatemeh Jafarbeigi; Mohammad Amin Samih; Mahdi Zarabi, et al. (Arthropods, 2014)
In addition to direct mortalities caused by acute concentrations of insecticides, some biological traits of target pests may be also affected by sublethal doses. The cotton whitefly, Bemisia tabaci (Hem: Aleyrodidae) is an important pest of a wide variety of agricultural crops across the world. The control of B. tabaci largely relies on wide application of chemical insecticides. In this study, we analyzed the life table parameters to evaluate the sublethal effect of three plant-derived insecticides (Fumaria parviflora (Fumariaceae), Teucrium polium (Lamiaceae), and Thymus vulgaris (Lamiaceae)) and two chemical insecticides (pymetrozin and neemarin) on B. tabaci. The whiteflies were allowed to oviposit on plants infected with each of the five insecticides using leaf-dip method. The data were analyzed using the age-stage two-sex life table. We found significant differences in the gross reproductive rate (GRR), the net reproductive rat (R0), the intrinsic rate of increase (r) and the finite rate of increase (λ) of treated whiteflies compared to control. Our results showed that some biological traits of B. tabaci are affected by sub-lethal doses of the plant-derived extracts and that these effects are comparable to those of chemical insecticides. Given the detrimental effects of chemical insecticides on human, environment and non-target organisms, plant-derived insecticides may provide valuable environmentally friendly tools for pest management programs.